Analisis Fikih Muamalah dan Peraturan Pemerintah No 28 Tahun 2020 tentang Pengelolaan Barang Milik Negara/Daerah terhadap Penyewaan Lahan PT KAI - Azmi Filhaq; Zaini Abdul Malik; Muhammad Yunus (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. In Islam, muamalah is an activity or activity carried out by humans to fulfill their daily needs, one of which is through renting or ijarah. Ijarah is a contract whose object is the exchange of benefits for a certain period, namely ownership of benefits in return or what can be called selling benefits. A lease or ijarah can be said to be valid if it meets certain pillars and conditions. The people of Langonsari Village, Pameungpeuk District, carry out activities for renting land belonging to PT KAI, so the author wants to know the suitability of the pillars and conditions according to muamalah jurisprudence or government regulations carried out by the people of Langonsari Village, Pameungpeuk District.The aim of this research is to determine the practice of leasing land owned by PT KAI and to analyze muamalah jurisprudence and Government Regulation No. 28 of 2020 concerning Management of State/Regional Property regarding the leasing of government-owned land in Langonsari Village, Pameungpeuk District, Bandung Regency. . The research framework focuses on the theory of ijārah contracts according to muamalah jurisprudence on the practice of leasing PT KAI land and the provisions of Government Regulation No. 28 of 2020 in Langonsari Village, Pameungpeuk District, Bandung Regency. This research uses a qualitative approach that is normative juridical in nature. The data sources for this research use primary data in the form of interviews and secondary data obtained from journals, articles, books and other sources.The research results found that in practice the people of Langonsari Village, Pameungpeuk District, Bandung Regency did not ask for permission to lease back PT KAI's land and did not pay rent to PT KAI, thereby causing losses to one of the parties, namely PT KAI. Therefore, the practice of leasing PT KAI's land in Langonsari Village, Pameungpeuk District, results in the ijāh contract being invalid according to muamalah jurisprudence as well as according to Government Regulations. Abstrak. Dalam Islam muamalah adalah suatu aktivitas atau kegiatan yang dilakukan oleh manusia untuk memenuhi kebutuhan hidupnya, salah satunya dengan sewa-menyewa atau ijarah. Ijarah adalah akad yang objeknya penukaran manfaat untuk masa tertentu, yaitu pemilikan manfaat dengan imbalan atau dapat disebut menjual manfaat. Sewa-menyewa atau ijarah dapat dikatakan sah apabila memenuhi rukun dan syarat-syarat tertentu. Masyarakat Desa Langonsari Kecamatan Pameungpeuk melakukan aktivitas sewa-menyewa lahan milik PT KAI sehingga penulis ingin mengetahui kesesuaian rukun dan syarat baik menurut fikih muamalah ataupun peraturan pemerintah yang dilakukan oleh masyarakat Desa Langonsari Kecamatan Pameungpeuk.Tujuan penelitian ini untuk mengetahui praktik sewa-menyewa lahan milik PT KAI dan untuk menganalisis fikih muamalah dan Peraturan Pemerintah No 28 Tahun 2020 Tentang Pengelolaan Barang Milik Negara/Daerah terhadap penyewaan lahan milik pemerintah di Desa Langonsari Kecamatan Pameungpeuk Kabupaten Bandung. Kerangka pemikiran pada penelitian berfokus mengenai teori akad ijārah menurut fikih muamalah terhadap praktik sewa menyewa lahan PT KAI dan ketentuan Peraturan Pemerintah No 28 Tahun 2020 di Desa Langonsari Kecamatan Pameungpeuk Kabupaten Bandung. Dalam penelitian ini menggunakan pendekatan secara kualitatif yang bersifat yuridis normatif. Sumber data penelitian ini menggunakan data primer berupa wawancara dan data sekunder yang diperoleh dari jurnal, artikel, buku, dan sumber lainnya. Hasil penelitian ditemukan bahwa dalam praktiknya masyarakat Desa Langonsari Kecamatan Pameungpeuk Kabupaten Bandung tidak meminta izin untuk menyewakan kembali lahan PT KAI dan tidak membayar uang sewa kepada PT KAI, sehingga menimbulkan kerugian pada salah satu pihak yaitu PT KAI. Oleh karena itu, praktik sewa menyewa lahan PT KAI di Desa Langonsari Kecamatan Pameungpeuk mengakibatkan akad ijarāh tidak sah menurut fikih muamalah begitupun menurut Peraturan Pemerintah